The Simulation of English Listening as Part of of the National Examination - Rabiatul Adawiah; Nihla Afdaliah; Uswatunnisa Uswatunnisa; Nur Fadillah Nurchalis; Muhyiddin Muhyiddin (STKIP Andi Matappa, 2021)
English is a subject in the national examination for senior high school students. As a foreign language, learning English gives some obstacles. This article is written to describe a project of community engagement namely a simulation of the English listening section as a part of the national examination. This project was conducted in Madrasah Aliyah Darud Da’wah Wal-Irsyad Baruga Majene by a collaborative team, which consists of the lecturers and the students of the English Language Education Department of Majene State Islamic College. The participants are third-grade students. The simulation was conducted as same as the real test using the Hot Potatoes. The result of the simulation showed that students’ achievement did reach the passing grade namely 55. There are ten basic competencies implied in fifteen number. But the students only can choose the correct answer from questions that reflected four bacis competencies with the highest average score namely 63. Unfortunately, the students cannot reach other competencies. It seems that the students need more practice and learning activities.